Estimating Ni valence with magnetometry in solid‐state reactive sintered yttrium‐doped barium zirconate. Issue 1 (2nd September 2021) - Knight, Michael; Jennings, Dylan; Ricote, Sandrine; Reimanis, Ivar
Abstract: Ni is known to have a significant impact on the sintering and microstructure evolution in yttrium‐doped barium zirconate (BZY) and yet details of its specific role remain unclear. The present study examined the valence state of Ni in solid‐state reactive sintered BZY prepared with different amounts of Ni, formulated for deliberate substitution of Ni for Zr : BaZr0.8−x Y0.2 Nix O3− δ with x = 0.005, 0.01, 0.02, 0.03, 0.04 (approx. 0.1 wt%, 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%). Quenching from 1500 ∘ C revealed transient BaY2 NiO5 phase was present in the microstructure for all concentrations of Ni studied here. Energy‐dispersive X‐ray spectroscopy identified Ni segregation in grain‐boundary regions upon completion of the solid‐state reactive sintering process, and magnetometry is used to show that low‐spin Ni 3+ predominantly substitutes for Zr 4+ . Abstract : Solid‐state reactive sintering at 1500°C results in Ni‐segregation at grain boundary regions of BaZr0.76 Y0.2 Ni0.04 O3− δ after decomposition of secondary BaY2 NiO5 phase. Magnetometry is utilized to estimate Ni oxidation state and electron resonance reveals local anisotropy in the Ni‐coordination environment.